The differences of Premarital Sexual Behavior between Teenage Girls in Public and Islamic Schools - Annisa Windi Soewastika; Fathia Anindya; Vira Nabila; Cut Berliananda Safitri (LPPM IAIN Parepare, 2021)
This study aims to measure adolescent premarital sex using a questionnaire based on scalogram analysis and compiled using the Guttman scale. Teenagers from public and Islamic schools have different sexual and religious knowledge. It may affect how they behave when undergoing a relationship (dating) with the opposite sex. This study involved students aged 13-19 years attending school in South Tangerang, had or currently involved in a dating relationship with the opposite sex, and at least had one premarital sexual behavior with a boyfriend. Based on low to high levels of intimacy (touching, kissing, petting, sexual intercourse), the results show that there are differences in sexual behavior between adolescent girls in public schools and Islamic schools, although not significantly. We can conclude that basically both teenagers from public and Islamic schools can have courtship relationships to the highest pre-sexual stage.